Analysis of the result of the consolidation of Public Accounting Information and its impact on decision-making of a financial and public nature in Colombia (2020)
The Public accounting information discharge an important role in the financial and public decision making, since through the collection of information made by the Contaduria General de la Nacion the nation's financial statements are prepared, delivered to the entities of the control to be analyzed reviewed and approved, in order to know in general the financial situation of old public entities being in turn the reflection on the accounting of the Colombian state. It is here that government agencies that have the power to make decisions regarding public policies do their job; The CGN provides all the information required to carry out financial analyzes that contribute each time to the achievement of the goals proposed by the state, both in the social and economic spheres, each time targeting financial growth and focusing on the distribution of wealth in a fair way, providing benefits to the most vulnerable; It is also important to highlight the mission of the state to control and monitor the management of public resources.